2024
DOI: 10.1590/1519-6984.252364
|View full text |Cite
|
Sign up to set email alerts
|

Morphophysiological changes of Acca sellowiana (Myrtaceae: Myrtoideae) saplings under shade gradient

Abstract: Understanding morphological and physiological changes under different light conditions in native fruit species in juveniles’ stage is important, as it indicate the appropriate environment to achieve vigorous saplings. We aimed to verify growth and morphophysiological changes under shade gradient in feijoa (Acca sellowiana (O. Berg) Burret) to achieve good quality saplings adequate to improve cultivation in orchards. The saplings were grown for twenty-one-month under four shading treatments (0%, 30%, 50%, and 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
3
2
0
Order By: Relevance
“…The reduced quantum yield of photosystem II in the non-shade treatment indicated that despite high PAR, not all sunlight absorbed was transformed into photochemical products, but this solar energy was dissipated as heat; it is well known that the excessive energy dissipation prevents photosynthetic apparatus disturbance in the thylakoids (Taiz et al, 2014). In addition to this, the higher ETR observed in species grown in full sunlight conditions in the Atlantic Forest demonstrates no damage in the reaction centers in photosystem I (Dos Anjos et al, 2012;Cerqueira et al, 2018;Silva et al, 2022). Our results regarding photosynthetic efficiency under shade treatments were congruent with previous research on the guabiroba plants ( Bartieres et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…The reduced quantum yield of photosystem II in the non-shade treatment indicated that despite high PAR, not all sunlight absorbed was transformed into photochemical products, but this solar energy was dissipated as heat; it is well known that the excessive energy dissipation prevents photosynthetic apparatus disturbance in the thylakoids (Taiz et al, 2014). In addition to this, the higher ETR observed in species grown in full sunlight conditions in the Atlantic Forest demonstrates no damage in the reaction centers in photosystem I (Dos Anjos et al, 2012;Cerqueira et al, 2018;Silva et al, 2022). Our results regarding photosynthetic efficiency under shade treatments were congruent with previous research on the guabiroba plants ( Bartieres et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…According to the results evaluated by Mielke and Schaffer (2010) [2], the biomass rose due to the partial effect of a high-light environment in E. uniflora seedlings. Similar morphological results were also established in Acca sewolliana [10] and Araucaria angustifolia [8], demonstrating that all these plants are sun-demanding species.…”
Section: Growth Traitssupporting
confidence: 79%
“…Previous studies portrayed that minimum radiance induces higher chlorophyll pigment content per mass unit [11], being part of the shade stress response. Various tree species displayed different chlorophyll levels under shade conditions [7,10,31]. Otherwise, although carotenoids are crucial in photoprotection under high-light regimes, some plants do not change these contents under light stress [31].…”
Section: Biochemical Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in leaf area under conditions of lower solar radiation can be considered phenotypic plasticity, as the increase in leaf area optimizes the interception of light rays and thus results in more efficient production of photoassimilates (Poorter et al, 2019;Reis et al, 2022;Silva et al, 2022). Furthermore, during the evaluations, we observed that plants with low water availability showed a reduction in leaf area, which remained stable even after supplying a greater amount of water, as observed in REC.…”
Section: Discussionsupporting
confidence: 54%